Assessment of field maintenance practices of coffea arabica among coffee farmers in Taraba State, Nigeria (2008)
This study was conducted to assess field maintenance practices on production of Coffea arabica among farmers in Sardauna Local Government Area of Taraba State, Nigeria during 2007. Data for the study were obtained from a systematic random sampling of eighty-eight coffee farmers through the use of well structured questionnaire. Data were analyzed using descriptive statistics and chi-square. Most (44.3%) of the respondents were 50-69 years old while 56.8 % of them belonged to 3-12 range of family size. Majority (98.9%) of the respondents claimed to be engaged in clearing of coffee farms, 97.7% coppiced old unproductive plot and the same figure harvested coffee berries. Extension workers' contact with farmers (36.4%) was low. The very serious constraints to Coffea arabica production were poor marketing (97.7%) and pricing (95.5%), inadequate' market information (89.8%), high labour cost (84.1%) and weak extension services 67.1%. The significant socio-economic variables that influence field maintenance practices of Coffea arabica include family size, farming experience, coffee beans price, and number of coffee farms maintained (p< 0.05). Good marketing strategies via farmers' group and improved extension contact would sustain Coffea arabica farming among farmers.